Self-presentation. Enterprise impression management as part of external reporting - Jaworska, Elżbieta; Bucior, Grzegorz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The way companies communicate with stakeholders is, among others, sharing of annual reports containing information on the corporate’s performance. The companies can present financial and non-financial information in a way that will serve their interests, using a variety of narratives. The aim of the study is to present the issues of impression management in the company’s financial reporting and the management strategies used to create the desired image. The method used was an analysis of available literature. The authors were primarily interested in the published research on: (1) the relationship between the following concepts: impression, image, reputation, self-presentation (2) impression management essence (3) impression management strategy in external reporting (4) directions of impression management usage in accounting and reporting. The study is a theoretical basis for further research covering the conduct of Polish companies in the context described
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 150-159
Keywords: Impression management; corporate image; self-presentation; reputation; disclosure strategies